Efetividade de vídeo educativo no conhecimento e habilidade de surdos acerca da ressuscitação cardiopulmonar: ensaio randomizado controlado - Galindo Neto, Nelson Miguel (2018)
The objective was to analyze the effectiveness of educational video use in the knowledge and ability of deaf people about cardiopulmonary resuscitation. This was a multi-method study, composed by a methodological research, for video construction and validation, and by randomized clinical trial, in which the educational video was used as the teaching strategy (for the intervention group) and the control group was exposed to the traditional lecture. It was carried out in three institutions that have deaf students, in Fortaleza-CE, with a sample obtained from the formula for studies with comparison between groups, composed of 113 participants, allocated randomly, from software R, in intervention group (56) and control device (57). Statistical tests were performed with a significance level of 5% and a 95% confidence interval and the ethical guidelines recommended by Resolution 466/12 were respected. The construction of the video took place from the reference of the Instructional Events of Gagné and the international guidelines on the theme. Its final version had seven minutes and thirty seconds, was composed by animation, audio narration and pounds and contemplated the steps that must be performed by the layman to provide the correct rescue to the victim of CRP. The content was validated by 22 nurses with expertise in cardiorespiratory arrest, and the appearance was evaluated by 16 deaf people. All items obtained a Content Validation Index of more than 0.8 and a concordance equal to or greater than 80%, so that the video was considered valid. Pre-test, post-test and post-test were performed after 15 days, theoretical and practical. The test scores after 15 days were higher than those of the pre-test (p> 0.001) and the medians of the practices of both groups were statistically superior after the interventions, with improvement from 7 to 10 in the control group and 6.25 to 10.5 in the intervention group. In the comparison of the knowledge between the groups there was similarity in nine of the 11 questions, with a better performance of the intervention group in the items that diverged (on the relay of the rescuer and the positioning of the victim in a rigid and flat place). As for the ability, in the test after 15 days the groups were similar in 10 of the 11 items, so that the intervention group obtained more answers regarding the performance of CPR at the correct speed. In the pre-tests, the control group had better answers. After 15 days, this superiority occurred in the intervention group, with statistical significance (p = 0.026 in the knowledge and p = 0.014 in the skill), so that the educational video about cardiopulmonary resuscitation is proven effective in increasing knowledge and skill of deaf people.